ULTRASTRUCTURAL AND MORPHOMETRIC CHANGES OF THE ENDOTHELIAL LAYER OF THE PULMONARY VASCULAR SYSTEM IN AN EXPERIMENTAL DIABETES MODEL - Dildora R. Sobirova ,; Abdulaziz A. Ahrorov , (Central Asian Journal of Medicine, 2025)
Diabetes mellitus, compared to other chronic and non-communicable diseases, causes significant damage to the vascular endothelium, potentially leading to severe and even fatal complications. Among elderly patients with diabetes and vascular complications, mortality rates range from 60% to 85%. The primary factor contributing to these complications is microangiopathy, a condition characterized by damage to small blood vessels.